Volatility spillovers between stock market and hedge funds: Evidence from Asia Pacific region - Sameen Fatima; Christopher Gan; Baiding Hu (Journal of Risk and Financial Management, 2022)
This paper investigates the nature of volatility spillovers between stock returns and hedge funds returns in twelve Asia Pacific countries in the 1997-2018 period. The sample period encompasses sub periods, 1997 Asia financial crisis, 2008 Global financial crisis and 2010 Eurozone crisis; these sub periods were characterised by financial upheavals. We apply the EGARCH methodology to model volatility and volatility spillovers in and between the markets. Our results show that the volatility of stock returns does not affect the volatility of hedge funds returns; however, there are inconsistent evidence of unidirectional volatility spillover from hedge funds to stock market returns.
Keywords: 650; EGARCH modelling; hedge funds; integration; stock returns; volatility spillovers